Spectrophotometric Determination of Ketotifen Fumarate in Pure and Pharmaceutical Preperations by Bromophenol Blue Reagent - O. S. Al-Khazrajy (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2016)
A spectrophotometric reliable, rapid and sensitive method has been developed and validated for  the determination Ketotifen fumarate  . A method was described for the determination of Ketotifen Fumarate  in pure form or pharmaceutical formulations, a colored ion-pair complex formation reaction among ketotifen fumarate and acid-dye bromophenol blue at pH 3.0 was used for the colorimetric determination of the drug. The complex formed was extracted into chloroform and the maximum absorbance of the solution was measured at 413 nm against blank. The calibration curve calculated obey Beer's law over the concentration range of 0.4-16 Î¼g/ml and the regression equation was A=0.069x+0.036 (R2=0.998). The recovery of the drug from a commercial tablet was 100.66-104.26 % of the label claim with a relative standard deviation of 0.867-1.472 %. The Sandell sensitivity values, limits of detection (LOD) and limit of quantification (LOQ) values have also been reported. No interference was observed from common excipients present in pharmaceutical formulations.